Идя из школы: Стихотворения / Валентин Берестов - Берестов Валентин Дмитриевич (Мол. гвардия, 1983)
Экземпляры: (20170511) / Инвентарный номер: 8672 / Цена: 0.40 / Сис.шифр: Р2 / Авт.знак: Б48 / ББК: Р2